Inventory management procedure at the molecular immunology center using the inventory reference model - Alemán de la Torre, Leisy (2023)
The research was carried out at the Molecular Immunology Center (CIM), a Cuban biotechnological institution dedicated to basic research, development, and manufacture of products for the treatment of cancer and other autoimmune diseases. The research problem addressed the poor management of inventories in companies, which is largely a consequence of the lack of procedures that enable the good performance of the logistics process. The objective of the research was the implementation of the inventory management procedure aimed at planning, managing, and controlling the necessary inventories without affecting the quality of the services, based on the analysis of indicators, description of logistics flows, and application of the Inventory Reference Model (MRInv). Different techniques and tools—including interviews, direct observation, surveys, documentary analysis, Minitab statistical software, and ABC analysis—were used. The result was the implementation of the inventory management procedure, which consisted of 10 steps that allow management to be carried out in an organized manner.